2008
DOI: 10.1111/j.1745-4565.2007.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Properties of Olive Leaf Extracts and Their Phenolic Compounds

Abstract: Olive (Olea europaea L.) leaf extracts were obtained using water or different organic solvents such as acetone, methanol and ethyl acetate. Antimicrobial activities of the extracts and some phenolic components were investigated to screen against 30 fungal strains (Alternaria alternata, Aspergillus chevalieri, A. chrysogenum, A. elegans, A. flavus [three strains], A. fumigatus, A. nidulans, A. niger [two strains], A. oryzae, A. parasiticus[four strains], A. tamari, P. verrucosum, A. versicolor, A. wentii, Fusar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 28 publications
2
31
0
2
Order By: Relevance
“…This oil is typically further refined or used in technical applications (Aparicio and Harwood 2013). In addition to LO acting as a hydrophobic agent, it also contains phenolic compounds with antifungal properties that may inhibit the rate of growth in a range of fungi (Korukluoglu et al 2008). It is well known that LO phenolic compounds are bioavailable and beneficially alter microbial activity and oxidative processes (Cicerale et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This oil is typically further refined or used in technical applications (Aparicio and Harwood 2013). In addition to LO acting as a hydrophobic agent, it also contains phenolic compounds with antifungal properties that may inhibit the rate of growth in a range of fungi (Korukluoglu et al 2008). It is well known that LO phenolic compounds are bioavailable and beneficially alter microbial activity and oxidative processes (Cicerale et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among them the phenolic compounds are especially important as plant defense systems, as are phytoanticipin or phytoalexin (Dixon and Paiva, 1995). The antimicrobial activities of phenolic compounds against bacteria (Herald and Davidson, 1983;Rauha et al, 2000) and fungi (Korukluoglu et al, 2008) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, the species is known for having medicinal properties, leaves are used for fighting against hypertension, atherosclerosis, diabetes, among others (Jänicke et al, 2003). The substances extracted from leaves are rich in polyphenols such as flavonoids (Pereira et al, 2007), which have antimicrobial activities (Korukluoglu et al, 2008). The by-products from residues of olive trees can also be used for food, cosmetics, and pharmaceuticals (Malik and Bradford, 2008).…”
Section: Introductionmentioning
confidence: 99%